MINDFULNESS YOGA AS AN ALTERNATIVE METHOD FOR PROMOTING PHYSICAL ACTIVITY AND WELL-BEING IN OLDER ADULTS: A COMMUNITY-BASED INTERVENTION - Herdhika Ayu Retno Kusumasari; Ronal Surya Aditya; Qory Tifani Rahmatika; Nanang Tri Wahyudi (Journal of Midwifery in Community (JMC), 2024)
Aging is associated with a natural decline in physical activity, leading to various health issues, including hypertension and decreased overall well-being.This community service project aimed to promote the importance of physical activity among older adults through mindfulness yoga and educational sessions in Desa Senggreng, Kabupaten Malang. The intervention was designed to encourage sustainable physical activity practices that can be continued independently at home.The intervention included educational sessions on the benefits of physical activity for older adults and yoga practice sessions tailored to their physical capabilities, then participants were provided with yoga instructional videos for continued practice at home. The blood pressure data indicated that 13 participants (32.5%) had hypotension, 17 participants (42.5%) had hypertension, and 10 participants (25%) had normal blood pressure. The intervention successfully increased awareness about the importance of physical activity in the aging population, and the provision of yoga videos empowered participants to continue practicing at home. The conclusion The mindfulness yoga intervention for older adults illustrates that yoga can be an effective alternative to promote physical activity, enhance health awareness, and support overall well-being in the elderly community